Autoimmune encephalitis associated with voltage‐gated potassium channels‐complex and leucine‐rich glioma‐inactivated 1 antibodies – a national cohort study. (25th May 2017) - Celicanin, M.; Blaabjerg, M.; Maersk‐Moller, C.; Beniczky, S.; Marner, L.; Thomsen, C.; Bach, F. W.; Kondziella, D.; Andersen, H.; Somnier, F.; Illes, Z.; Pinborg, L. H.
Abstract : Background and purpose: The aim of this study was to describe clinical and paraclinical characteristics of all Danish patients who tested positive for anti‐voltage‐gated potassium channels (VGKC)‐complex, anti‐leucine‐rich glioma‐inactivated 1 (LGI1) and anti‐contactin‐associated protein‐2 antibodies in the serum/cerebrospinal fluid between 2009 and 2013 with follow‐up interviews in 2015 and 2016. Methods: We evaluated antibody status, symptoms leading to testing, course of disease, suspected diagnosis and time of admission as well as diagnosis and treatment. All magnetic resonance imaging, electroencephalography and 18 F‐fluorodeoxyglucose positron emission tomography scans were re‐evaluated by experts in the field. Results: A total of 28/192 patients tested positive for VGKC‐complex antibodies by radioimmunoassay and indirect immunofluorescence; 17 had antibodies to LGI1 and 6/7 of the available cerebrospinal fluids from these patients were seropositive. These 17 patients all had a clinical phenotype appropriate to LGI1 antibodies. The remaining 11 were LGI1 negative ( n = 4) or not tested ( n = 7). Of these, two had a phenotype consistent with limbic encephalitis. The remaining phenotypes were Guillain–Barré syndrome, Creutzfeldt–Jakob disease, neuromyotonia and anti‐ N ‐methyl‐D‐aspartate receptor encephalitis. Magnetic resonance imaging abnormalities were demonstrated in 69% of the LGI1‐positive patients. Two patients with normal magnetic resonance imaging demonstrated temporal lobe hypermetabolism using 18 F‐fluorodeoxyglucose positron emission tomography. Abnormal electroencephalography recordings were found in 86% of the patients. Upon follow‐up (median 3.2 years), the median modified Rankin Scale score of anti‐LGI1‐positive patients was 2 and only two patients reported seizures in the past year. Conclusions: Patients diagnosed with anti‐LGI1 autoimmune encephalitis increased significantly from 2009 to 2014, probably due to increased awareness. In contrast to seropositive anti‐VGKC‐complex patients, all anti‐LGI1‐positive patients presented with a classical limbic encephalitis. The majority of patients recovered well. Abstract : Clickhere for the corresponding questions to this CME article.